The impact of therapeutic alliance in physical therapy for chronic musculoskeletal pain: A systematic review of the literature - Kinney, Meredith; Seider, Jasmine; Beaty, Amanda Floyd; Coughlin, Kaitlin; Dyal, Maximilian; Clewley, Derek (Physiotherapy theory and practice, 2020)
To systematically determine the specific impact of therapeutic alliance (TA) on chronic musculoskeletal pain, identify factors influencing TA between physical therapists and patients with chronic musculoskeletal pain, and determine the working definition of TA across studies. Data Sources: Databases, including PubMed, CINHAL, and Embase, were searched from inception to January 2017. Study Selection: The initial search resulted in 451 papers. After screening, seven studies were identified that examined the role of TA on chronic pain (> 12 weeks) management in physical therapy settings. Data Extraction: Authors extracted data into tables. Risk of bias was assessed using Cochrane Collaboration methodology. Data Synthesis: Three studies examined the influence of a strong TA coupled with physical therapy on pain outcomes. Four studies identified factors that positively and negatively influenced TA. The working definition of TA was identified in each study. Conclusions: Emerging evidence suggests that for individuals participating in physical therapy for chronic musculoskeletal pain, a strong TA may improve pain outcomes. In order to facilitate a strong TA, physical therapists must understand factors that positively and negatively influence the relationship. Studies demonstrate that the definition of TA remains consistent as it transitions to the physical therapy setting.